Analysis and implementation of high‐gain non‐isolated DC–DC boost converter. Issue 11 (1st September 2017) - Muhammad, Musbahu; Armstrong, Matthew; Elgendy, Mohammed A.
Abstract : High step‐up DC–DC converters are increasingly required in many industrial applications. Conventional topologies operate at extreme duty cycle, high‐semiconductor voltage stress, switching loss, and diode reverse recovery problems. This study presents a new non‐isolated high gain, boost converter operating with a modest duty cycle by integrating a coupled inductor and switched capacitor technique. Importantly, the structure of the high‐voltage side, together with the switched capacitor, reduces the voltage stress of the power switch to less than one third of the output voltage, which in turn helps to reduce the conduction loss by using a low on‐resistance (Rds‐on ) switch. The diode voltage stress is less than the output voltage which facilitates faster recovery. Furthermore, the converter employs a passive clamp circuit to recycle the leakage energy. The main switch achieves zero current switching (ZCS) turn‐on performance and all diodes achieve (ZCS) turn off reducing reverse recovery related losses. As a result, the circuit exhibits high efficiency performance; which is essential for most modern power electronic applications. In this study, the operational principle and performance characteristics of the proposed converter is presented and validated experimentally with a 250 W, 20V input voltage/190V output voltage prototype circuit.